2020
DOI: 10.3390/cancers12123755
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Subsequent Malignant Neoplasms in Patients with History of Testicular Germ Cell Tumor

Abstract: Although genetic changes may be pivotal in the origin of cancer, cellular context is paramount. This is particularly relevant in a progenitor germ cell tumor and its differentiated mature teratoma counterpart when it concerns tumor heterogeneity and cancer dormancy in subsequent second malignancies (subsequent malignant neoplasms (SMNs)). From our tumor registry database, we identified 655 testicular germ cell tumor (TGCT) patients who developed SMNs between January 1990 and September 2018. Of the 113 solid or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 50 publications
(28 reference statements)
1
23
0
Order By: Relevance
“…We revisit seminal experiments of other cancers supporting the idea that cancer is a stem cell disease. We reiterate recent experiments that affirm a close relationship between a primary TGCT and a second subsequent malignant neoplasm (SMN) separated by years, if not decades, and between a mature teratoma and a somatically transformed malignant neoplasm within the same tumor in the same patient [8]. In principle, these experiments validate a universal cancer theory based on pertinent clinical observations.…”
Section: Introductionsupporting
confidence: 77%
“…We revisit seminal experiments of other cancers supporting the idea that cancer is a stem cell disease. We reiterate recent experiments that affirm a close relationship between a primary TGCT and a second subsequent malignant neoplasm (SMN) separated by years, if not decades, and between a mature teratoma and a somatically transformed malignant neoplasm within the same tumor in the same patient [8]. In principle, these experiments validate a universal cancer theory based on pertinent clinical observations.…”
Section: Introductionsupporting
confidence: 77%
“…Importantly, TGCT is a preeminently curable cancer (>90% cure rate) even when it is advanced and metastatic, in part because we know how to deal with its genotypes and how to treat its phenotypes [15][16][17]. Hence, in a mixed TGCT containing embryonal carcinoma and teratoma, both have the same genetic marker (i.e., i(12p)) and a similar if not identical genetic makeup due to their common clonal origin.…”
Section: Testicular Cancermentioning
confidence: 99%
“…In many respects, the indolent and dormant nature of yolk sac tumor and teratoma belies their treacherous eventual outcome. Importantly, ensconced within a residual, supposedly innocuous teratoma after chemotherapy are dormant and covert progenitor stem cells that may reawaken and relapse as a yolk sac tumor and/or a somatically transformed tumor [40].…”
Section: Very Late Recurrencementioning
confidence: 99%
“…Umbreit et al [40] found that about half of a variety of subsequent malignant neoplasms (SMN), including lung cancer, colon cancer, and kidney cancer, in 42 patients with a previous history of TGCT contained a common genetic biomarker for TGCT, namely isochromosome 12p [i(12p)] (12%) or 12p gain (38%), by fluorescent in situ hybridization analysis. These SMN comprising non-TGCT occurred about 18 years (range 0.4-53.6 years) after an initial diagnosis of TGCT.…”
Section: Second Malignanciesmentioning
confidence: 99%